PELATIHAN PEMANFAATAN GAMIFIKASI DALAM PEMBELAJARAN BAGI GURU SD DI DESA GOMBANG - Khoridatul Huda, Moh.; Puspitasari, Desi (Proceedings of Annual Conference on Community Engagement, 2023)
Implementing gamification in education can be done online and face-to-face. Training on the use of gamification in learning, such as the one held at SD Desa Gombang, Slahung, is essential to improve the competence and creativity of educators. It is in line with the demand to innovate in the face of the current era of disruption. This research employed an Asset-Based Community Development (ABCD) approach. The results of this study underscore the critical role of gamification in education transformation. Gamification can increase student learning interest, and teacher competence, and integrate technology into learning. It is a step towards establishing technology-based educational institutions ready to compete in the digital era. Through training and implementing gamification, educators can better prepare students for a future marked by rapid technological change.